The Little Data Book on Private Sector Development 2007 - World Bank (World Development Indicators, 2007)
The Little Data Book on Private Sector Development 2007 is one of a series of pocket-sized books intended to provide a quick reference to development data on different topics. The Little Data Book on Private Sector Development 2007 provides data for more than 20 key indicators on business environment and private sector development in a single page for each of the World Bank member countries and other economies with populations of more than 30,000. These more than 200 country pages are supplemented by aggregate data for regional and income groupings. The data topics include: economic and social context, business environment, private sector investment, finance and banking, infrastructure. It is intended as a quick reference for users of World Development Indicators, WDI Online, and the Atlas of Global Development. The book also includes data from the World Bank's Doing Business project and Enterprise Surveys